Expression of 5-lipoxygenase in differentiating human skin keratinocytes. - Janssen-Timmen, Uwe; Vickers, P. J.; Wittig, Ulrike; Lehmann, Wolf-Dieter; Stark, Hans-Jürgen; Fusenig, Norbert; Rosenbach, T.; Rådmark, O.; Samuelsson, B.; Habenicht, Andreas (Proceedings of the National Academy of Sciences of the United States of America, 1995)
We studied the expression of arachidonate 5-lipoxygenase (5-LO) in a cell line of human keratinocytes (HaCaT) and in normal human skin keratinocytes in tissue culture. In undifferentiated keratinocytes 5-LO gene expression was low or undetectable as determined by 5-LO mRNA, protein, cell-free enzyme activity, and leukotriene production in intact cells. However, after shift to culture conditions that promote conversion of prokeratinocytes into a more differentiated phenotype, 5-LO gene expression was markedly induced in HaCaT cells and, to a lesser extent, in normal keratinocytes. These results show that 5-LO gene expression is an intrinsic property of human skin keratinocytes.